2002
DOI: 10.1074/jbc.m202465200
|View full text |Cite|
|
Sign up to set email alerts
|

Hypercholesterolemia Promotes a CD36-dependent and Endothelial Nitric-oxide Synthase-mediated Vascular Dysfunction

Abstract: Numerous studies have implicated either the presence or absence of CD36 in the development of hypertension. In addition, hypercholesterolemia is associated with the loss of nitric oxide-induced vasodilation and the subsequent increase in blood pressure. In the current study, we tested the hypothesis that diet-induced hypercholesterolemia promotes the disruption of agonist-stimulated nitric oxide generation and vasodilation in a CD36-dependent manner. To test this, C57BL/6, apoE null, CD36 null, and apoE/CD36 n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
33
0

Year Published

2002
2002
2015
2015

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 53 publications
(36 citation statements)
references
References 52 publications
3
33
0
Order By: Relevance
“…In some cell types, expression of caveolin-1 has been shown to be necessary for plasma membrane targeting of CD36, and disruption of caveolae may effect some CD36 dependent functions (Ring, Le Lay, Pohl, Verkade, & Stremmel 2006,Vistisen, Roepstorff, Roepstorff, Bonen, van Deurs, & Kiens, 2004,Frank, Lee, Park, Tandon, Scherer, & Lisanti,. 2004,Pohl, Ring, Korkmaz, Ehehalt, & Stremmel, 2005,Kincer, et al, 2002, Dorahy, Lincz, Meldrum, & Burns, 1996. The partitioning of CD36 to specific plasma membrane domains may facilitate interaction with signaling partners that are essential to CD36 dependent responses.…”
Section: Cd36 Structure and Expressionmentioning
confidence: 99%
“…In some cell types, expression of caveolin-1 has been shown to be necessary for plasma membrane targeting of CD36, and disruption of caveolae may effect some CD36 dependent functions (Ring, Le Lay, Pohl, Verkade, & Stremmel 2006,Vistisen, Roepstorff, Roepstorff, Bonen, van Deurs, & Kiens, 2004,Frank, Lee, Park, Tandon, Scherer, & Lisanti,. 2004,Pohl, Ring, Korkmaz, Ehehalt, & Stremmel, 2005,Kincer, et al, 2002, Dorahy, Lincz, Meldrum, & Burns, 1996. The partitioning of CD36 to specific plasma membrane domains may facilitate interaction with signaling partners that are essential to CD36 dependent responses.…”
Section: Cd36 Structure and Expressionmentioning
confidence: 99%
“…2). Recently it was shown that hypercholesterolemia in mice results in CD36-mediated cholesterol depletion of caveolae, followed by translocation of eNOS from caveolae and subsequent inactivation of the enzyme (42). Thus, eNOS activity is directly related to the cholesterol content of caveolae.…”
Section: Table I Plasma Lipid and Lipoprotein Analysismentioning
confidence: 99%
“…This observation might be the result of disruption of the signal transduction complex containing eNOS, caveolin-1, and other molecules required for eNOS activation. Recent work by Kincer et al 58 has shown that CD36, a class B scavenger receptor associated with caveolae, was probably responsible for this effect. 58 This observation is important in view of the fact that in hypercholesterolemic patients or animal models, impairment of endothelium-derived relaxation is observed.…”
Section: Caveolae Caveolin-1 and Atherosclerosismentioning
confidence: 99%
“…Recent work by Kincer et al 58 has shown that CD36, a class B scavenger receptor associated with caveolae, was probably responsible for this effect. 58 This observation is important in view of the fact that in hypercholesterolemic patients or animal models, impairment of endothelium-derived relaxation is observed. 59 -61 In agreement with this finding, Feron et al 62 have shown that exposure of endothelial cells to serum from hypercholesterolemic patients promotes an increase in the caveolin-1-eNOS interaction.…”
Section: Caveolae Caveolin-1 and Atherosclerosismentioning
confidence: 99%